Transportation movement with containers in Iraqi harbors (Journal of the College of Education for Women, 2019)
The use of containers in transportation leads to the reduction in time and effort of the process of loading and unloading of goods as well as protecting the goods from damage and breakage and to reduce the financial costs.. This development has led also to make changes in the sizes and capacity of ships, therefore changes in the ports must be taken place where they must be provided with an appropriate depth for such vessels, that means the increase in the depth of ports and the establishment of wide storage yards and to provide appropriate mechanisms for handling process.In this study, the researcher has dealt with this type of transport business in Iraqi ports, namely:1- Khur Al-Zubair port.2- Um Qaser port.In order to specify the readiness and the appropriateness of Iraqi ports for such kind of transport in terms of their number of specialized berths, their depths, the mechanisms used in the handling process and the percentage of the containers of the total foreign trade in order to find out whether the ad hoc of Iraqi ports are suitable for the global development taking place in the area.